The conservative logic of public-private relationship in education that counters democratic management and the quality of public education (Práxis Educativa, 2020)
This paper aims to analyze the public-private relationship established between the Manaus Municipal Education Secretariat (SEMED-Manaus) and the Ayrton Senna Institute (IAS) with regard to democratic management and improving the quality of education. The theoretical-methodological categories of historical-dialectical materialism - totality, mediation and contradiction - engendered the bibliographic research, documentary research and the organization and analysis of the collected information. The legal and political frameworks of the constitutional principle of Democratic management of Public Education, the analysis of education policies and the conceptions of the quality of education were mediated by the conceptions and approaches of Gadotti (2014), Gentili (2018), Peroni, Oliveira and Fernandes (2009), Cabral Neto and Silva (2001). The analysis revealed that conservatism, present in Brazilian politics, allowed regressions to the achievements of public education and that the quality of education, under the parameters of SEMED-Manaus and IAS partnership, is a commodity that provides individualized access and exclusive distribution of services.Keywords: Manaus and IAS. Democratic management. Quality of education.